Adaptation and initial psychometric study of the anxiety and fear of COVID-19 scale in the United Kingdom population - Morgado-Toscano, Cristina; Allande-Cussó, Regina; Fagundo-Rivera, Javier; Navarro-Abal, Yolanda; Climent-Rodríguez, Jose Antonio; Gómez-Salgado, Juan (Frontiers in Psychiatry, 2023)
Objective: The aim of the study was the initial psychometric study to validate the Anxiety and Fear of COVID-19 (AMICO) Assessment Scale in the general population of the UK population. Materials and Methods: A descriptive, cross-sectional, psychometric validation and descriptive study was conducted, performing univariate and bivariate analyses, as well as exploratory and confirmatory factor analysis. Results: The sample was 658 people living in the United Kingdom over 16 years. Of the total, 80.5% were female, with a mean age of 48.25 years (SD =14.861). A mean score for the AMICO scale of 4.85 (SD= 2.398) was obtained, with a range of scores from 1 to 10. The study of percentiles and quartiles allowed for the identification of three proposed levels of anxiety. Conclusions: The AMICO_UK scale is reliable to measure the presence of anxiety and fear related to the COVID-19 disease in the UK population. The majority of the UK population presented low levels of anxiety and fear at the time the scale was administered.